ANALISIS PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK PADA KEDAI WEDHANG SUGUHAN PERIODE 2022 - Aditya Rahman; Martinus Robert Hutauruk; Siti Rohmah; Agus Riyanto (University of Widya Gama Mahakam Samarinda, 2024)
Aditya Rahman, Analysis of the Implementation of Accounting Standards for Entities Without Public Accountability at the Wedhang Suguhan Shop, with Supervisor I Mr. Dr. Martinus Robert Hutauruk, SE., MM, AK, CA and Supervisor II Mrs. Siti Rohmah, S.E., M.Ak. The purpose of this research is to find out and analyze the financial reports of Kedai Wedhang Suguhan in accordance with the SAK ETAP implementation. The method used is the Qualitative Method by comparing the financial reports of Accounting Standards for Entities Without Public Accountability (SAK ETAP) with the financial reports of Kedai Wedhang Suguhan. The results of this research indicate that the presentation of financial reports at the Wedhang Suguhan shop is not in accordance with the Accounting Standards for Entities Without Public Accountability (SAK ETAP). The Wedhang Suguhan shop's financial report for the 2022 period presents a profit and loss report. Meanwhile, the presentation of Accounting Standards for Entities Without Public Accountability includes presentations including Balance Sheet Financial Reports, Profit and Loss Reports, Equity Change Reports, Cash Flow Reports and Notes to Financial Reports. Using the comparative method, a percentage of 20% can be found to be inappropriate.